2014
DOI: 10.14233/ajchem.2014.16582
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Bioherbicidal Properties of Essential Oils of Thymus fallax Fish & Mey., Origanum vulgare L. and Mentha dumetorum Schult.

Abstract: INTRODUCTION Recently, much research has been conducted on the increased food production that will be needed for the rapidly increasing world population and on synthetic pesticides, with the goal of reducing damage to the environment and human health. Unfortunately, substantial yield losses occur due to insects and plant diseases caused by fungi, bacteria and viruses 1,2. Synthetic chemicals (e.g., herbicides, fungicides and insecticides) are widely used in the control of plant diseases, pests and weeds. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…All studies focused of testing the phytotoxic activities on dicot model plant species and the results showed strong activity in each of these studies, although different EO doses were used. The herbicidal effect was evaluated on seed germination as well as on root length respective to seedling development [5,8,27,28,36,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies focused of testing the phytotoxic activities on dicot model plant species and the results showed strong activity in each of these studies, although different EO doses were used. The herbicidal effect was evaluated on seed germination as well as on root length respective to seedling development [5,8,27,28,36,38].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific studies noted potential phytotoxic effect of O. vulgare which were tested on various dicot plant species (Sinapis arvensis L., Phalaris canariensis L., Lepidium sativum and Raphanus sativus. ; Abutilon theophrasti Medik., Agrostemma githago L., and Medicago sativa L.) [13,25,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…After applying Thymus spp. EO, other weed species such as A. retroflexus , Avena fatua L., Datura stramonium L., Lepidium sativum L. and Agrostemma githago L. were also significantly affected, either at germination or at the seedling growth stage [ 6 , 105 ]. These findings indicate that different species of Thymus ( T. fallax Fisch.…”
Section: Examples Of Lamiaceae Species With Bioherbicidal Potentialmentioning
confidence: 99%
“…Different studies tested them on a variety of weed species with varying results. Onaran et al [ 105 ] found that M. dumetorum EO suppressed the germination of A. theophrasti better than other tested EOs such as O. vulgare and T. fallax . Another test used the EO from a specific Peppermint cultivar ( Mentha × piperita L. cv.…”
Section: Examples Of Lamiaceae Species With Bioherbicidal Potentialmentioning
confidence: 99%
“…Therefore, researchers focus on developing new bio-pesticide against weed and controling of plant diseases by using new active molecules such as seconder metabolites (Onaran et al, 2014;Yılar and Kadıoğlu, 2016;Onaran, 2016). Secondary metabolites are naturally contained in plants and their effectiveness on diseases and harmful weeds have been studied by isolating the allelochemicals with the potential of biological activity from the plants.…”
Section: Introductionmentioning
confidence: 99%